Exploring the anticancer and antibacterial potential of naphthoquinone derivatives: a comprehensive computational investigation - Meem, Mehnaz Hossain; Yusuf, Sumaiya Binte; Al Abbad, Sanaa S.; Rahman, Shofiur; Al-Gawati, Mahmoud; Albrithen, Hamad; Alodhayb, Abdullah N.; Uddin, Kabir M. (Frontiers in Chemistry, 2024)
This study investigates the potential of 2-(4-butylbenzyl)-3-hydroxynaphthalene-1,4-dione (11) and its 12 derivatives as anticancer and biofilm formation inhibitors for methicillin-resistant staphylococcus aureus using in silico methods. The study employed various computational methods, including molecular dynamics simulation molecular docking, density functional theory, and global chemical descriptors, to evaluate the interactions between the compounds and the target proteins. The docking results revealed that compounds 9, 11, 13, and ofloxacin exhibited binding affinities of −7.6, −7.9, −7.5, and −7.8 kcal mol−1, respectively, against peptide methionine sulfoxide reductase msrA/msrB (PDB: 3E0M). Ligand (11) showed better inhibition for methicillin-resistant staphylococcus aureus msrA/msrB enzyme. The complex of the 3E0M-ligand 11 remained highly stable across all tested temperatures (300, 305, 310, and 320 K). Principal Component Analysis (PCA) was employed to evaluate the behavior of the complex at various temperatures (300, 305, 310, and 320 K), demonstrating a total variance of 85%. Convergence was confirmed by the eigenvector’s cosine content value of 0.43, consistently displaying low RMSD values, with the minimum observed at 310 K. Furthermore, ligand 11 emerges as the most promising candidate among the compounds examined, showcasing notable potential when considering a combination of in vitro, in vivo, and now in silico data. While the naphthoquinone derivative (11) remains the primary candidate based on comprehensive in silico studies, further analysis using Frontier molecular orbital (FMO) suggests while the Egap value of compound 11 (2.980 eV) and compound 13 (2.975 eV) is lower than ofloxacin (4.369 eV), indicating their potential, so it can be a statement that compound 13 can also be investigated in further research.